(3eONd GJNGP GdbQGQGJs - (3YHO GdZaGQ(B, (3Mfajs ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2007)
(3ebOeI aj GdGOGQI GdeGdjI h OhQ GdhXjaI GdeGdjI HGdeTQhY , GdJMdjd GdeGdj h GdJNWjW GdeGdj h GdQbGHI , SjGSGJ JhRjY GdGQHGM , eaghe h NUGFU GdGfaGb GdQCSeGdj h CSGdjH Jbjje GdGbJQGMGJ GdGSJKeGQjI aj XQha GdKHGJ h GdJCcO , GdeaGVdI Hjf GdGbJQGMGJ GdGSJKeGQjI aj XQha GdJZjjQ h YOe GdJCcO , JcdaI GdGehGd h GJNGP bQGQGJ GdGSJKeGQ , GdJehjd GdOGNdj h GdNGQLj h efgL bjGS JcdaJg , GdJcdaI GdeQLMI ddCehGdcefgL ddJbjje h GdeaGVdI deTQhYGJ GdGSJKeGQ h GNjQG GdJehjd bUjQ h Whjd GdGLd(B.s
Keywords: (3GJNGP GdbQGQGJs; (3GdGOGQIs; (3GdeGdjIs